2005
DOI: 10.1007/s00595-004-3086-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Endoscopic Resection of Left Ventricular Tumors

Abstract: Operative TechniqueThe operation was performed via a median full sternotomy. Cardiopulmonary bypass was established with either bicaval or single right atrial cannulation and single arterial cannulation. While using cardioplegic protection, the left atrium or ascending aorta was opened. Under direct vision, the inside of the left ventricle was scarcely visible through the mitral or aortic valve. As a result, an endoscope (XQ240; Olympus, Tokyo, Japan) was inserted into the left ventricular cavity through the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was followed by semi-rigid endoscopes in four [7, 9, 21, 29], flexible endoscopes in three [2, 3, 30] and mixture of rigid and flexible endoscopes in one study [11]. In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Misumi et al reported two cases of endoscopic resection of left ventricular tumors through the mitral valve and the aortic valve. 4 Li et al reported a technique using video-assisted cardioscopy to remove a left ventricular myxoma. [5][6][7] When the tumors are located on the valve surface, it is not diffi cult to perform a resection.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have performed direct resection of the tumor under endoscopic visualization using a rigid‐type thoracoscope or mediastinoscope . Others have visualized and removed the tumor with a snare with a flexible endoscope or gastrointestinal fiberscope and avoided the use of a rigid type with a straight shaft because of its inflexibility and poor handling . In our case, we used a video‐assisted rigid endoscope with a flexible head.…”
Section: Discussionmentioning
confidence: 99%